In-Vitro α-amylase, α-glucosidase Inhibitory Activities and In-Vivo Anti-Hyperglycemic Potential of Different Dosage Forms of Guduchi (Tinospora Cordifolia [Willd.] Miers) Prepared With Ayurvedic Bhavana Process - Sharma, Rohit; Bolleddu, Rajesh; Maji, Jayanta K.; Ruknuddin, Galib; Prajapati, Pradeep K. (Frontiers in Pharmacology, 2021)
Guduchi (Tinospora cordifolia [Willd.] Miers) is a flagship rejuvenating herb of Ayurveda with reported anti-diabetic potential. In the present study, different dosage forms of Guduchi stem (growing on neem tree) were developed by adopting Ayurvedic pharmaceutical process of Bhavana (levigation). Guduchi Churna (GC) was subjected to 07 times Bhavana separately with its own extracted juice, decoction and potable water, and dosage forms namely Svarasa Bhavita Guduchi Churna (SBGC), Kwatha Bhavita Guduchi Churna (KBGC), and Jala Bhavita Guduchi Churna (JBGC) were prepared. The present study was aimed to evaluate the role of Bhavana on the potentiation of therapeutic properties of Guduchi. Sequential solvent extracts (5%, 10%, 15% and 25%) of GC, SBGC, KBGC and JBGC were prepared in different solvents [phosphate buffer, hexane, dichloromethane (DCM), chloroform] and screened for the α-amylase and α-glucosidase inhibitory activity. The results revealed that phosphate buffer and DCM extracts of SBGC exhibited strong α-amylase inhibitory potential (>80% inhibition at 25% concentration) followed by KBGC, JBGC and GC with reference to the standard acarbose. In α-glucosidase inhibitory activity, maximum inhibition was observed in DCM and chloroform extracts of SBGC (>85% inhibition at 25% concentration), followed by KBGC (>80% inhibition at 25% concentration), JBGC and GC. In vivo anti-hyperglycemic studies were carried out by oral glucose tolerance test in Swiss albino mice. Test drugs (JBGC, KBGC, SBGC) treated groups showed marginal decrease of blood glucose levels in normo glycemic mice. However, the blood glucose level in test drug JBGC, KBGC and SBGC treated groups was still within normal range in overnight fasted mice. In oral glucose tolerance test, among all dosage forms SBGC (51.08%) produced a pronounced anti-hyperglycemic effect followed by KBGC (42.57%) at a dose of 520mg/kg. The GC, JBGC, KBGC and SBGC samples were also standardized using berberine (a well established anti-diabetic compound) as a marker compound by HPTLC fingerprint analysis. Findings of the present study indicate that SBGC and KBGC can be used in the treatment of diabetes mellitus and gives supporting evidence to Ayurvedic claims that the Bhavana process has pharmaceutico-therapeutic significance in Ayurvedic drug development.